2016
DOI: 10.3126/jist.v21i1.16058
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of Rhododendron Campanulatum D. Don and Associated Tree Species along the Elevational Gradient of Manaslu Conservation Area, Nepal

Abstract: Climate change is affecting the forest ecosystems worldwide. Impacts of climate change are more perceptible at higher altitudes and can be easily detected along the elevational gradient. The main aim is to study the impact of elevation on the population structure of Rhododendron campanulatum D. Don and associated trees species at Manaslu Conservation Area, central Nepal. A total of 30 quadrats were sampled from 3600-4100 meter above sea level (m asl.) at altitudinal difference of 100 m with 5 quadrates in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…These values were derived as the value for a species expressed as a percentage of the sum of those values for all the species of the community. Those species having the maximum IVI were considered as dominant species [15,16]. To determine the biotic factors affecting the growth of B. utilis, the association or correlation among species was determined by calculating the most dominant associated tree species with B. utilis.…”
Section: Species Dominance Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These values were derived as the value for a species expressed as a percentage of the sum of those values for all the species of the community. Those species having the maximum IVI were considered as dominant species [15,16]. To determine the biotic factors affecting the growth of B. utilis, the association or correlation among species was determined by calculating the most dominant associated tree species with B. utilis.…”
Section: Species Dominance Analysismentioning
confidence: 99%
“…According to Mir et al (1), germination of B. utilis takes place under low temperature with fully imbibed state and it is regulated by temperature and interaction of photoperiod, which contradicts down the gradient in present study site. Rana et al [16] also reported that regeneration of B. utilis is affected by the thick vegetation, which is least favored by light demanding species hence leading to replacement by shade tolerant species. Zhu et al [19] also reported that open area favors the regeneration of the tree species.…”
Section: Dominant Tree Speciesmentioning
confidence: 99%
“…A few dead standing and absence of dead fallen trees in the Tinjure area indicated more human encroachment. Density, total basal area and IVI of Rhododendron companulatum along the elevation gradient (3600-4100 m) of Manaslu conservation area were 140-940 tree/ha; 1.0-10.81 m 2 /ha and 138-180, respectively (Rana et al, 2016). In Deurali forest, Quercus semecarpifolia was dominant and Rhododendron arboreum was codominant trees whereas in Basantapur, Castanopsis tribuloides was dominant and Symplocos ramosisisima was co-dominant trees (Table 3).…”
mentioning
confidence: 92%
“…Despite its importance, studies on fine root dynamics are limited in the tropical forest ecosystem mainly due to difficulties in root sampling and controversies in determining the fine root biomass, although other aspects of the forest of Nepal were reported elsewhere (Bhujel et al, 2019;Bhandari et al, 2018;Rana et al, 2016). The study on nutrient concentration, nutrient stock, and uptake in fine root in Sal (Shorea robusta Gaertn.)…”
Section: Introductionmentioning
confidence: 99%